Parking System: A Comprehensive Management Solution for Small Parking Facilities - Claudisnei, Claudisnei (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study presents the design and implementation of a Parking Management System specifically developed for small-scale parking facilities. The system aims to automate core operations such as vehicle tracking, rate calculation, and payment processing to reduce inefficiencies common in manual management. Developed using Delphi and the Paradox database, the system applies a modular two-tier architecture integrating independent modules for vehicle entry, exit, billing, and reporting. Data validation, automated fee computation, and structured reporting features ensure accurate transactions and transparency. The interface is designed for non-technical users, emphasizing clarity, reliability, and operational speed. Implementation results show improved efficiency, reduced processing time, and enhanced financial accuracy. Despite technological constraints related to scalability and legacy database architecture, the system remains a cost-effective and practical solution for small parking operators. Future improvements could include migration to modern relational databases, integration with mobile and web platforms, and adoption of emerging technologies such as IoT sensors and AI-based analytics to support smart, data-driven parking management.